The connection between children's knowledge and use of grapho‐phonic and morphemic units in written text and their learning at school. (20th November 2013) - Bryant, Peter; Nunes, Terezinha; Barros, Rossana
<x xml:space="preserve">Abstract</x> Background Most psychologists who study children's reading assume that their hypotheses are relevant to children's success at school. This assumption is rarely tested. Aims The study's aims were to see whether two successful measures of the processes underlying children's learning to read and write are related to their success in English, science, and mathematics as measured by school assessments. Sample Data from the Avon Longitudinal Study of Parents and Children were available for between 2, 500 and 5, 900 children (in different analyses) on their use of graphophonic and morphemic units in reading and writing and on their achievement in Key Stage 2 and Key Stage 3 assessments. Method Hierarchical multiple regressions assessed the relationship between children's use of grapho‐phonic and morphemic units at 8‐ and 9‐years and their performance in the Key Stage 2 (11‐years) and Key Stage 3 (14‐years) assessments in English, mathematics, and science. Results The children's grapho‐phonic and morphemic skills predicted their achievement in all three subjects at Key Stage 2, 3 years later, and at Key Stage 3, 5 years later, even after stringent controls for differences in age and IQ. The connection between the two types of orthographic skills and the children's educational success was largely mediated by their reading ability as measured by standardised tests. Conclusions Children's knowledge and use of grapho‐phonic and morphemic rules has a lasting effect on the progress that they make at school. This knowledge has an impact on their reading ability which in turn affects their success in learning about English, mathematics and science.